Local feminist perspectives as transformation levers for greater gender equality: Synthesis study - Jacqueline Götze; Stephan Klingebiel; Maryam Khalid (German Institute of Development and Sustainability (IDOS), 2025)
The significance of gender equality needs to be spotlighted since women and LGBTQIA* communities are prone to become victims of violence and have limited participation in political and decision-making processes. The approaches of feminist development policies and feminist foreign policies have been criticised for their potential inapplicability to diverse contexts and for perpetuating paternalistic or neo-colonial behaviours. The global rise of right-wing policies has influenced politics, prompting researchers on feminist policies to critically examine their limitations and the ways they have been institutionalised. The present study builds on the expertise, knowledge and experiences of partners from Ghana, India and Ukraine. It introduces local feminist perspectives as levers for transformative change for greater gender equality that can produce context-specific alternative approaches to development processes by addressing prevailing norms and practices, and thereby enhance access to resources and improve the political participation of women, girls and members of the LGBTQIA* communities. This synthesis study identifies common themes, challenges and opportunities across the three case studies prepared by the partner organisations through a combination of deductive and inductive processes. We have developed a matrix of 13 criteria, which can be categorised into five thematic clusters that include: intersectionality, special characteristics of local feminisms and gender (in)equalities, multi-directional flow of norms, challenges and opportunities for gender-transformative change, and future of gender-transformative policies. Key findings reveal persistent barriers faced by local feminist perspectives in influencing policy, decision-making and gender norms due to limited possibilities and restricted opportunities.
Keywords: 320; Gender; multilateral development policy